Treatment of femoropopliteal lesions with the AngioSculpt scoring balloon: results from the Heidelberg PANTHER registry - Lugenbiel, Ira; Heilmeier, Britta; Cebola, Rita; Müller, Oliver J.; Katus, Hugo (Vasa, 2018)
. Background: Treatment of calcified femoropopliteal lesions remains challenging, even in the era of drug-eluting balloon angioplasty. Lesion recoil and dissections after standard balloon angioplasty in calcific lesions often require subsequent stent implantation. Additionally, poor patency rates in calcified lesions despite the use of drug-eluting balloons may be due to the limited penetration depth of the antiproliferative drug in the presence of vascular calcium deposits. Therefore, preparation of calcified lesions with the AngioSculpt™ scoring balloon might be a valuable option either as a stand-alone treatment, followed by drug-eluting balloon angioplasty or prior to subsequent stent deployment. Patients and methods: In this retrospective, single centre registry, 124 calcified femoropopliteal lesions were treated in 101 subsequent patients. All patients were treated with scoring balloon angioplasty, either alone, in combination with drug-eluting balloons, or prior to stent deployment. The primary outcome was safety and technical success during the index procedure as well as patency at six and 12 months, as evaluated by duplex sonography. Results: Successful scoring was safely performed in all 124 lesions with the AngioSculpt™ balloon. Overall primary patency after 12 months was 81.2 %. Patency rates did not differ significantly between the three treatment strategies. Degree of calcification did not predict patency. Improved clinical outcomes (Rutherford-Becker class and ankle-brachial index) were also observed in the study cohort. Conclusions: Preparation with the AngioSculpt™ scoring balloon offers a safe and valuable treatment option for calcified femoropopliteal lesions.